Various Strategies to Increase Sensitivity in Inclusive Schools - Husnul Istiqomah; Sunardi Sunardi; Joko Yuwono (Teknodika, 2026)
Sensitivity toward students with disabilities is a crucial element in fostering an inclusive learning environment. However, schools labeled as inclusive are not always able to demonstrate adequate sensitivity in their daily educational practices. This study aims to identify and analyze strategies for enhancing sensitivity toward students with disabilities in inclusive schools through three main dimensions: teacher strategies, student strategies, and school policy strategies. The study employed a qualitative approach with a case study design at an inclusive elementary school in Banjar Regency, South Kalimantan. The participants consisted of 20 teachers selected purposively, including 6 classroom teachers, 2 subject teachers, and 12 special education teachers. Data were collected through an open-ended questionnaire administered via Google Forms and analyzed using thematic analysis. Data trustworthiness was maintained through source triangulation across participant groups. The findings revealed three main strategies for enhancing sensitivity. Teacher strategies were manifested in instructional adjustments, differentiated teaching strategies, and role modeling in fostering empathy. Student strategies were reflected in collaboration, positive social contact, dialogue on diversity, and the habituation of nondiscriminatory interaction. School policy strategies were strengthened through supportive leadership, reflective forums, the habituation of inclusive values, and partnerships with parents and the community. This study confirms that sensitivity toward students with disabilities is not merely an individual attitude, but rather a collective school competence shaped pedagogically, socially, and institutionally. The implications of the study indicate that strengthening sensitivity can be achieved through realistic and low-cost measures, such as teacher reflection forums, peer support systems, the habituation of inclusive values, and the strengthening of partnerships with parents.